2021
DOI: 10.1007/s12028-021-01394-y
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Brain Tissue Oxygenation Monitoring and Association with Mortality Following Severe Traumatic Brain Injury

Abstract: Background:The aim of this study was to describe the utilization patterns of brain tissue oxygen (PbtO 2 ) monitoring following severe traumatic brain injury (TBI) and determine associations with mortality, health care use, and pulmonary toxicity. Methods:We conducted a retrospective cohort study of patients from United States trauma centers participating in the American College of Surgeons National Trauma Databank between 2008 and 2016. We examined patients with severe TBI (defined by admission Glasgow Coma S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…PbtO 2 represents the second most commonly used invasive neuromonitor after ICP and the two together are the most widely published MMM combination (4). Bundling PbtO 2 and ICP/CPP compared to managing ICP/CPP in isolation has been explored in multiple retrospective analyses, both in TBI and SAH populations, and found improved mortality and functional outcomes associated with combined therapy with no increase in length of stay or serious adverse events including ARDS (95,99,(120)(121)(122)(123). Though large prospective trial data is lacking, a 2015 small multicenter study found that PbtO 2 and ICP/CPP guided therapy was associated with more aggressive ICP control and higher CPP with a trend toward improved functional outcomes at 6 months compared to ICP management alone (124).…”
Section: Brain Tissue Oxygen Partial Pressurementioning
confidence: 99%
“…PbtO 2 represents the second most commonly used invasive neuromonitor after ICP and the two together are the most widely published MMM combination (4). Bundling PbtO 2 and ICP/CPP compared to managing ICP/CPP in isolation has been explored in multiple retrospective analyses, both in TBI and SAH populations, and found improved mortality and functional outcomes associated with combined therapy with no increase in length of stay or serious adverse events including ARDS (95,99,(120)(121)(122)(123). Though large prospective trial data is lacking, a 2015 small multicenter study found that PbtO 2 and ICP/CPP guided therapy was associated with more aggressive ICP control and higher CPP with a trend toward improved functional outcomes at 6 months compared to ICP management alone (124).…”
Section: Brain Tissue Oxygen Partial Pressurementioning
confidence: 99%
“…97 Similar trends have been observed with large observational studies, but the results of the BOOST-3 trial (NCT03754114) are eagerly anticipated. 98 DC, which is non-permanent removal of a skull bone flap, can be used as a primary procedure when performed for evacuation of a mass lesion to control postoperative ICP. This is particularly attractive for acute subdural hematomas (ASDHs) due to the high incidence of cerebral edema and IHT.…”
Section: Open Accessmentioning
confidence: 99%
“… 97 Similar trends have been observed with large observational studies, but the results of the BOOST-3 trial (NCT03754114) are eagerly anticipated. 98 …”
Section: Difficult Neurosurgical Decisionsmentioning
confidence: 99%
“…[ 73 ] Although promising results have also been demonstrated in large observational studies, routine adoption of B tp O 2 monitoring will likely be influenced by the anticipated BOOST-3 trial (NCT03754114). [ 42 , 49 ]…”
Section: Identifying Neuroworseningmentioning
confidence: 99%